Pengaruh Iklan di Facebook Terhadap Minat Beli Siswa di Kabupaten Rokan Hulu - Maysaroh, Maysaroh; Fitri, Amelia; Qurniawati, Eka Fitri (Journal of Social Media and Message, 2022)
This study aims to determine the effect of advertising on Xiaomi mobile phones on Facebook toward buying interest in adolescent students at SMPN 1 Kepenuhan Hulu, Rokan Hulu District. The theory used is the AIDDA theory which explains that attention, interest, desire, decision and action are in the communication process. The method used in this study is a quantitative method with a simple random sampling technique and the number of samples is 100 respondents who are teenagers from State Junior High School 1 (SMPN1) Kepenuhun Hulu. The results of the study indicate that there is a significant impact between the advertising variables toward the buying interest of teenagers at SMPN 1 Kepenuhan Hulu. The result of the coefficient of determination of the Xiaomi mobile phone advertisement on the buying interest of young students at SMPN 1 Kecepatan Hulu is 23%.